Carbon fiber felt scaffold from Brazilian textile PAN fiber for regeneration of critical size bone defects in rats: A histomorphometric and microCT study - Pereira, Kauê Alberto [UNESP]; Torquato, Letícia Cavassini [UNESP]; Maciel, Clarissa Carvalho Martins [UNESP]; Nunes, Camilla Magnoni Moretto [UNESP]; Mantovani, Ludmilla Oliveira [UNESP]; Almeida, Nátaly Domingues [UNESP]; Lopes, Sergio Lucio Pereira Castro [UNESP]; de Vasconcellos, Luana Marotta Reis [UNESP]; Jardini, Maria Aparecida Neves [UNESP]; Marcuzzo, Jossano Saldanha; De Marco, Andrea Carvalho [UNESP] (Wiley, 2024)
The objective of the present study was to evaluate the carbon fiber obtained from textile PAN fiber, in its different forms, as a potential scaffolds synthetic bone. Thirty-four adult rats were used (Rattus norvegicus, albinus variation), two critical sized bone defects were made that were 5 mm in diameter. Twenty-four animals were randomly divided into four groups: control (C)—bone defect + blood clot, non-activated carbon fiber felt (NACFF)—bone defect + NACFF, activated carbon fiber felt (ACFF)—bone defect + ACFF, and silver activated carbon fiber felt (Ag-ACFF)—bone defect + Ag-ACFF, and was observed by 15 and 60 days for histomorphometric, three-dimensional computerized microtomography (microCT) and mineral apposition analysis. On histomorphometric and microCT analyses, NACFF were associated with higher proportion of neoformed bone and maintenance of bone structure. On fluorochrome bone label, there was no differences between the groups. NACFF has shown to be a promising synthetic material as a scaffold for bone regeneration.
Keywords: biocompatible materials; bone regeneration; carbon fiber; tissue engineering